Pengaruh Pengendalian Internal, Moralitas Individu, dan Whistleblowing System terhadap Pencegahan Fraud - Qorirah, Nuzul Fajri; Syofyan, Efrizal (Universitas Negeri Padang, 2024)
This study aims to empirically examine the effect of internal control, individual morality, and whistleblowing system on fraud prevention. This research was conducted at the Regional Apparatus Organization (OPD) of Padang City with a sample of 38 OPDs. This study uses primary data obtained by distributing questionnaires directly to respondents, namely the General Treasurer, Head of Finance, and Finance Section Staff. The sampling technique used purposive sampling technique. The analysis method used in this research is multiple regression analysis method using SPPS (Statistical Product and Service Solution) version 25. The results showed that internal control has a significant positive effect on fraud prevention, while individual morality and whistleblowing system have no significant effect on fraud prevention.